KEBIJAKAN STRATEGIS DAN LOCAL WISDOM TATA KELOLA HUTAN DAN LAHAN DI PROVINSI RIAU - Zamhasari Zamhasari; T fahrul Gafar (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2021)
This study seeks to analyze strategic policies and local wisdom that exist in local communities in governancing and managing forests in Riau Province. This research uses qualitative method with case study research type. This study concludes that forest and land governances in Riau is still poor. The government has also not seriously implemented the strategy that has been made to resolve the case of forest and land fires. Increasing the budget in preventive efforts must be accompanied by efforts to improve budget governance that is more transparent and accountable. The role of the local government in overcoming unresolved land degradation conditions must be a priority that should not be ignored.